Jumping off Arnstein's ladder: social learning as a new policy paradigm for climate change adaptation - and Collins, Kevin; Ison, Ray (Environmental Policy and Governance, 2009)
Participation of citizens, groups, organizations and businesses is now an essential element to tackle climate change effectively at international, European Union, national and local levels. However, beyond the general imperative to participate, major policy bodies offer little guidance on what this entails. We suggest that the dominance of Arnstein's ladder of citizen participation in policy discourses constrains the ways we think about, and critically the purposes we ascribe to, participation in a climate change context. We suggest an alternative framing of climate change, where no single group has clear access to understanding the issue and its resolution. Thus adaptation is fundamentally dependent on new forms of learning. Drawing on experiences of social learning approaches to natural resource managing, we explore how a commitment to social learning more accurately embodies the new kinds of role, relationship, practice and sense of purpose required to progress adaptive climate change agendas and practices. Copyright extcopyright 2009 John Wiley & Sons, Ltd and ERP Environment.
Keywords: Arnstein's ladder; Climate change; Co-evolutionary adaptation; Natural resource management; Participation; Social learning